Menopause hormone therapy and the risk of thromboembolic disease - Kotarski, Jan; Barczyński, Bartłomiej; Kwaśniewski, Wojciech (Menopause Review/Przegląd Menopauzalny, 2011)
Decision on implementing hormone therapy in perimenopausal woman has to be based on analysis of potential risks and benefits of such treatment. Although rarely observed, one of the most serious complication of hormonal therapy is thromboembolic disease. Many published clinical trials: Women’s Health Initiative (WHI), Heart and Estrogen/Progestin Replacement Study (HERS), Heart and Estrogen/progestin Replacement Study follow-up (HERS II), Estrogen in Venous Thromboembolism Trial (EVTET), Women’s International Study of long Duration Oestrogen after Menopause (WISDOM) showed a 2- to 3- fold increased risk of thromboembolism in women taking oral hormonal therapy. In practical terms, eight additional thromboembolic events would be expected in every 10.000 women of normal weight, aged 50-59 years, taking combined estrogen-progestogen hormonal therapy for 12 months. The risk of thromboembolism is mainly associated with metabolic effects of estrogens but new data show possible procoagulating activity of some progestogens. The risk appears to be more prominent in women who start oral hormonal therapy (during first six months of treatment) and is increased during first 2 years of treatment. Transdermal delivery of estrogens appears to be a safer way of hormonal treatment and is not associated with increased risk of thromboembolism. Several studies confirm that also synthetic steroid, tibolone may diminish the risk of venous thrombosis. Nevertheless, transdermal 17β-estradiol, due to its safe profile, should be recommended as the drug of choice for majority of women during perimenopause.